A-5 Brain-Derived Neurotrophic Factor Val66Met and Neuropsychological Functioning Following Early Childhood Traumatic Brain Injury. (30th August 2021) - Treble-Barna, Amery; Kurowski, Brad; Martin, Lisa; Pilipenko, Valentina; Taylor, Gerry; Wade, Shari; Yeates, Keith
Abstract: Objective: The present study examined the differential effect of the brain-derived neurotrophic factor (BDNF) Val66Met polymorphism on neuropsychological functioning in children with traumatic brain injury (TBI) relative to children with orthopedic injury (OI). Method: Participants were drawn from a prospective, longitudinal study of children who sustained a TBI (n = 69) or OI (n = 72) between 3 and 7 years of age. Children completed a battery of neuropsychological measures targeting attention, memory, and executive functions at four time points spanning the immediate post-acute period to 18 months post-injury. Children also completed a comparable age-appropriate battery of measures approximately 7 years post-injury. Parents rated children's executive functioning at all time points. Results: Longitudinal mixed models revealed a significant allele status x injury group interaction for verbal fluency (p = 0.007) and a non-significant trend for parent-rated dysexecutive behaviors (p = 0.069), and cross-sectional models at 7 years post-injury revealed a non-significant trend for the allele status x injury group interaction for fluid reasoning skills (p = 0.074). Post hoc analyses suggested a consistent pattern of poorer neuropsychological functioning in Met carriers relative to Val/Val homozygotes in the TBI group; in contrast, the opposite trend was observed in the OI group. Conclusions: The results suggest a differential effect of the BDNF Val66Met polymorphism on verbal fluency, dysexecutive behaviors, and fluid reasoning skills in children with early TBI relative to OI, and that the Met allele—associated with reduced activity-dependent secretion of BDNF—confers risk for poorer neuropsychological functioning in children with TBI.